Pengaruh Sikap, Norma Subjektif dan Persepsi Kontrol Perilaku Terhadap Minat Kepemilikan Kartu Kredit - Idris Idris; Arief Bowo Prayoga Kasmo (Jurnal Manajemen dan Bisnis Indonesia, 2017)
This study as a purpose to determine the effect of attitudes, subjective norms and perceived behavioral control to intention of credit card ownership. The object of this study is customer of Bank which do not have credit card. This research was conducted on 105 respondents by using quantitative descriptive approach. Data analysis is processed by using SEM-PLS (Partial Least Square) and data is processed by using SmartPLS tools. The results of this study indicate that the attitude proved to have a significant effect on intention of credit card ownership because it has a T-value above 1.96 that is 3,372, subjective norms have not proven significant effect to intention of credit card ownership because it has T - value below 1.96 that is 1.537, perceived behavioral control found the results proved to have a significant effect to intention of credit card ownership because it has T - value above 1.96 that is 3,689. Therefore, the result of this study stated that attitude and perceived behavioral control has significantly effect to intention of credit card ownership, whereas subjective norm has no significant effect to intention of credit card ownership. Keywords: Attitude, Subjective Norms, Behavior Control Perception, Intention to ownership, credit card